Mechanisms for efficient voting with private information about preferences - Dirk Engelmann; Veronika Grimm (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2008)
We experimentally study behavior in a simple voting game where players have private information about their preferences. With random matching, subjects overwhelmingly follow the dominant strategy to exaggerate their preferences, which leads to inefficiency. We analyze an exogenous linking mechanism suggested by Jackson and Sonnenschein (2007) as well as repeated interaction in different settings, which could allow endogenous linking mechanisms to evolve. We find that applying the exogenous mechanism captures nearly all achievable efficiency gains, whereas repeated interaction leads to significant gains in truthful representation and efficiency only in a setting where players can choose their partners.
Keywords: A13; C72; C91; C92; D64; D72; D80; 330; Experimental Economics; Mechanism Design; Implementation; Linking; Bayesian Equilibrium; Efficiency; Wahlverhalten; Asymmetrische Information; Mechanism; Spieltheorie; Test